Transformation of the 8p’s to 8c’s - A Customer Centric Approach - Rani, T. Suchitra; Menon, Dhanya (Indian Journal of Marketing, 2005)
Innovation today has become a corporate buzzword. It has been proved that in any field of endeavor, innovation is the hallmark of success. Business is no exception and innovation plays a very important role in defining marketing strategies. The Traditional 4Ps of marketing have given way to 8Ps, which in turn, are being transformed by new-age marketing strategists to 8Cs. Marketers are now focusing on the customer experience and maintaining relationships in order to gain a competitive edge. Therefore, a customer-centric approach would enable organizations to build successful brands and improve profitability.